Medical students’ perspectives about traditional and integrated learning programs at University of Bisha, Saudi Arabia - El-Alashkar, Ayman M.; Hashish, Abdullah A.; Aboregela, Adel; Sonpol, Hany; Metwally, Ashraf Salah; Sinbel, Ahmed; Al-Shahrani, Abdullah M. (International Journal Of Community Medicine And Public Health, 2023)
Background: Students’ approaches to learning are central to the process of learning. There is strong debate about the efficiency of traditional learning programs (TLP) and integrated learning programs (ILP) in medical schools. TLP is easy for the students being passive learners and for the tutors playing the role of sage on the stage. ILP is mainly student-centered. It is essential to know the perspectives of medical school students about both programs as they used to apply TLP in the 1st year and started ILP in the 2nd year. Methods: This study adopted a quantitative research methodology. We addressed the 3rd-year medical students at the College of Medicine, University of Bisha, KSA. An online survey using Google forms was applied for data collection. The study was performed from August 2019 to June 2021. Results: Agreement with the integrated program (80.8%) exceeded the traditional (48.5%) especially in improving communication skills, dealing with new technologies, reinforcement of competencies in the research field, and to lesser extent for its suitability to be applied in medical schools nowadays, development of desired doctor skills to deal with patients and for provision of good approach for medical practice, and lastly for its suitability to identify and deal with the community needs. There was no statistical significance between the 2 programs regarding support of professionalism values. The disagreement of ILP (19.2%) was much lower than TLP (51.5%). Conclusions: Integrated learning program becomes an innovative tool for learning in medical schools with excellent compliance among medical students.